2018
DOI: 10.1017/etds.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

A generalization of the simulation theorem for semidirect products

Abstract: We generalize a result of Hochman in two simultaneous directions: Instead of realizing an effectively closed Z d action as a factor of a subaction of a Z d+2 -SFT we realize an action of a finitely generated group analogously in any semidirect product of the group with Z 2 . Let H be a finitely generated group and G = Z 2 ⋊ H a semidirect product. We show that for any effectively closed H-dynamical system (Y, f ) where Y is a Cantor set, there exists a G-subshift of finite type (X, σ) such that the H-subaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…More generally, [Jea15b] has shown that polycyclic groups admit strongly aperiodic subshifts of finite type. • Work of Barbieri and Sablik [BS16] shows that any group of the form Z 2 ⋊ H, where H has decidable word problem, admits a strongly aperiodic SFT. This is a very broad collection of groups since it includes Z 2 × H for any H with decidable word problem, as well as the group Sol 3 ∼ = Z 2 ⋊ Z.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, [Jea15b] has shown that polycyclic groups admit strongly aperiodic subshifts of finite type. • Work of Barbieri and Sablik [BS16] shows that any group of the form Z 2 ⋊ H, where H has decidable word problem, admits a strongly aperiodic SFT. This is a very broad collection of groups since it includes Z 2 × H for any H with decidable word problem, as well as the group Sol 3 ∼ = Z 2 ⋊ Z.…”
Section: Introductionmentioning
confidence: 99%
“…Free groups cannot possess strongly aperiodic SFTs [MS85], and a finitely generated and recursively presented group with an aperiodic SFT necessarily has a decidable word problem [Jea15]. Groups that are known to admit a strongly aperiodic SFT are Z 2 [Rob71] and Z d for d > 2 [CK96], fundamental groups of oriented surfaces [CGS17], hyperbolic groups [CGSR17], discrete Heisenberg group [SSU20] and more generally groups that can be written as a semi-direct product G = Z 2 φ H, provided G has decidable word problem [BS19], and amenable Baumslag-Solitar groups [EM20].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a recent interest in symbolic dynamics on more general contexts, such as where the lattice Z 2 is replaced by the Cayley graph of an infinite, finitely generated group. Using again the existence of strongly aperiodic SFTs, the domino problem was shown to be undecidable, apart from Z d , on some semisimple Lie groups [18], the Baumslag-Solitar groups [2], the discrete Heisenberg group (announced, [20]), surface groups [10,1], semidirect products on Z 2 [6] or some direct products [4], polycyclic groups [13], some hyperbolic groups [11]. .…”
Section: Introductionmentioning
confidence: 99%